Existing Problems of Teaching Organic Chemistry in Academic Lyceums and Ways to Overcome Them (Journal of Pedagogical Inventions and Practices, 2022)
The purpose of this work is to interest students of the academic lyceum in organic chemistry and find solutions to the problems they face in order to quickly master science.